Bringing EU law back down to Earth. Issue 4 (December 2022) - O'Brien, Charlotte
Abstract: Traditional approaches to teaching EU law can seem almost deliberately alienating; there is a lot of incomprehensible stodge that students are told they 'just have to get through' before they can really begin. So courses start with memorising technical terminology, institutional facts and then some principles that, without context, can just seem like more jargon. By the time they move on to case-law and legislation, the idea that these things are useful domestic tools has long since vanished. Instead, a contextual approach mitigates a trio of risks that have beset traditional EU law teaching – the risks of excessive positivism, excessive abstraction and excessive black-letter lawyering. Context requires critical engagement with, rather than simple absorption of, law; it makes the law accessible and applicable; and it involves socio-legal and interdisciplinary methods and materials. It is, of course, risky in different ways – but we should have a greater appetite for risks related not to cognitive stagnation, but to intellectual challenge.